Transformasi Manajerial Madrasah Menghadapi Disrupsi Artificial Intelligence: Analisis Kebijakan Dan Adab Akademik Berbasis Pesantren - Ulfatul Munawaroh; Khoirul Anwar; Ainur Rofiq (Universitas Pakuan, 2026)
MADRASAH MANAGERIAL TRANSFORMATION IN FACING ARTIFICIAL INTELLIGENCE DISRUPTION : AN ANALYSIS OF PESANTREN-BASED POLICY AND ACADEMIC ETHICS The purpose of this study is to analyze madrasah managerial policies in responding to the utilization of Artificial Intelligence (AI) in secondary education and its impact on the integrity of students' academic adab (ethics) at MTs Al Amiriyyah Blokagung Banyuwangi. The method used is a qualitative method with an exploratory case study design involving 15 key informants, consisting of 1 headmaster, 1 vice-headmaster of curriculum, 3 subject teachers, and 10 students. Data collection techniques were conducted through in-depth interviews and document studies, which were then analyzed using an interactive analysis model through data condensation, data display, and conclusion drawing stages. The results show a policy gap between macro regulations focusing on infrastructure digitalization and the unavailability of ethical-pedagogical guidelines for technology use in madrasah. At the empirical level, the convenience of AI triggers an increase in instantism and academic plagiarism in student assignments. As preliminary findings, the madrasah management designed local mitigation strategies in the form of a draft AI ethics protocol, assessment restructuring through the oral munaqasyah method, and teacher capacity building as digital mediators. This study concludes that the reconstruction of integrative internal policies based on pesantren values is absolutely necessary to maintain a balance between algorithmic capability and the nobility of academic adab